Functional Fc receptors are crucial in antibody-mediated protection against cytomegalovirus - Bootz, Anna; Reuter, Nina; Nimmerjahn, Falk; Britt, William J.; Mach, Michael; Winkler, Thomas H. (European Journal of Immunology, 2024)
Human cytomegalovirus is a medically important pathogen. Previously, using murine CMV (MCMV), we provided evidence that both neutralizing and nonneutralizing antibodies can confer protection from viral infection in vivo. In this study, we report that serum derived from infected animals had a greater protective capacity in MCMV-infected RAG−/− mice than serum from animals immunized with purified virus. The protective activity of immune serum was strictly dependent on functional Fcγ receptors (FcγR). Deletion of individual FcγRs or combined deletion of FcγRI and FcγRIV had little impact on the protection afforded by serum. Adoptive transfer of CD115-positive cells from noninfected donors demonstrated that monocytes represent important cellular mediators of the protective activity provided by immune serum. Our studies suggest that Fc–FcγR interactions and monocytic cells are critical for antibody-mediated protection against MCMV infection in vivo. These findings may provide new avenues for the development of novel strategies for more effective CMV vaccines or antiviral immunotherapies.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Antibodies; Cytomegalovirus; Fc receptor; Monocytes